2022
DOI: 10.1038/s41379-022-01073-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of deep learning assistance for the pathological diagnosis of gastric cancer

Abstract: Previous studies on deep learning (DL) applications in pathology have focused on pathologist-versus-algorithm comparisons. However, DL will not replace the breadth and contextual knowledge of pathologists; rather, only through their combination may the benefits of DL be achieved. A fully crossed multireader multicase study was conducted to evaluate DL assistance with pathologists’ diagnosis of gastric cancer. A total of 110 whole-slide images (WSI) (50 malignant and 60 benign) were interpreted by 16 board-cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In recent years, artificial intelligence has achieved unprecedented development, and the application of this frontier technology in the field of medicine has gradually become a new trend. Recent studies have demonstrated promising results of deep learning algorithms in recognizing various lesions using WSIs ( 12 , 14 , 15 , 21 , 22 ). As for EC, the increasing diagnostic workload of endometrial biopsy specimens calls for the development of new models with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, artificial intelligence has achieved unprecedented development, and the application of this frontier technology in the field of medicine has gradually become a new trend. Recent studies have demonstrated promising results of deep learning algorithms in recognizing various lesions using WSIs ( 12 , 14 , 15 , 21 , 22 ). As for EC, the increasing diagnostic workload of endometrial biopsy specimens calls for the development of new models with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, most of the proposed computational pathology tools are restricted to research use only (RUO) and can only be used to provide a complementary analysis to that performed by a pathologist. In [40], [41], it was shown that the combination of computational pathology and human pathologists has the potential to improve accuracy and efficiency in gastric cancer diagnosis. However, with the use of computational pathology, remarkable progress has been made beyond RUO.…”
Section: Computational Pathologymentioning
confidence: 99%
“…However, unrelated features and redundancy were still observed. A case study was conducted to assess the pathologist’s deep learning competence in diagnosing gastric infections [ 22 ]. In this study, 16 professional pathologists inferred a total of 110 whole slide images (WSI) containing 50 malignant and 60 benign tumors with and without deep learning assistance.…”
Section: Introductionmentioning
confidence: 99%